One very short gap; SHOW ME SHORTS FILM FESTIVAL - CROOT, James (The Press (Christchurch, N.Z.), 2010)
The 2010 line-up has some of the most controversial subject matter to date, with films that focus on graffiti, vampires, youth suicide, sexual preference for soft toys, abortion, converting religions, losing your virginity to a sex worker, bullying, alcoholism, and adultery. Paul Campion has had two films in our programme previously [Killer Hamsters and Eel Girl] and he is currently in post-production on his first feature - The Devil's Rock.